Parental experiences of the informed consent process in randomized clinical trials-A Nordic study - Mogensen Nina; Kreicbergs Ulrika; Albertsen Birgitte K; Lähteenmäki Päivi; Heyman Mats; Harila Arja (WILEY, 2025)
Background: Randomized clinical trials (RCTs) are an essential part of improving acute lymphoblastic leukemia (ALL) treatment. This population-based questionnaire study investigated parents' experiences of the informed consent process in the RCTs within the Nordic NOPHO (Nordic Society of Paediatric Haematology and Oncology) ALL2008 trial.
Procedure: Parents in Sweden, Denmark, and Finland whose child was alive and in first remission after end of therapy and who were asked to participate in any RCT in the ALL2008 protocol, were asked to complete 15 questions/items regarding their experience of the RCT consent process.
Results: A total of 483 parents of 279 children met the inclusion criteria and answered the study questionnaire. Most (91%) agreed/strongly agreed to having received sufficient information to make a well-informed decision, felt confidence in the study design (86%), and thought that the process was satisfactory (86%). Those who did not consent reported a generally more negative experience of the process. More than a third of all parents and over half of parents who had refused participation felt that it was burdensome to decide. Most parents (66%) in general, and one-third of those with children 8 years or older, reported that their child was not involved in the process.
Conclusions: Parents were in general satisfied with the informed consent process, although many parents, particularly those who refused participation, reported it as burdensome to make the decision concerning RCT. Fewer than expected of the school-aged children were involved in the decision process, which calls for attention on how children are included in the consent procedure in clinical trials.